E-Card Stock Web Based Using Barcode for Fast Kitchen Concept - Sh Salleh, Muhammad; Mohsin, Muhammad Izzuddin; Mazlan, Nur Sazlin Syafika; Masandig, Hannes (Multidisciplinary Applied Research and Innovation, 2022)
E-Card Stock Web Based Using Barcode for Fast Kitchen Concept Sdn. Bhd. (FKC) is built to assist in the stock management of products and raw materials that are more efficient, systematic, and easy to use. It aims to upgrade the inventory management method that has been used by FKC using manual system. The manual system refers to the method by using stock-card for recording information incoming and outgoing of products and raw materials. The use of this old method leads to duplication of information or inaccurate information such as the current volume of product stocks and raw materials. Therefore, this project is used to assist FKC in digital stock management. The development method used was a waterfall model to produce the system. At the end of this project, E-Card Stock Web Based Using Barcode for Fast Kitchen Concept Sdn. Bhd. has been developed and used by the FKC to manage their inventory of products and raw materials better and more efficiently. A survey has been conducted and found that 85% of the respondent totally agree that the implementation of the new system is better than the old manual method. However, this project have minor drawback in which the interface for this system support only for Windows and it is important for this system to be able to run on android platform which is the main interaction for modern entrepreneur.